Loose Commitment in Medium-Scale Macroeconomic Models: Theory and an Application - Davide Debortoli; Junior Maih; Ricardo Nunes (Norges Bank, 2010)
This paper proposes a method and a toolkit for solving optimal policy with imperfect commitment in linear quadratic models. As opposed to the existing literature, our method can be employed in medium- and large-scale models typically used in monetary policy. We apply our method to the Smets and Wouters (2007) model, where we show that imperfect commitment has relevant implications for the interest rate setting, the sources of business cycle fluctuations, and welfare.
hdl:11250/2497436
Keywords: C32; E58; E61; 330; commitment; discretion; linear-quadratic